The comparison of cardiovascular risk factors prevalence among Catholics and Seventh-day Adventists living in southern Poland - Majda, Anna; Zalewska-Puchała, Joanna; Bodys-Cupak, Iwona; Kamińska, Alicja; Suder, Marcin (Nursing in the 21st Century, 2018)
THE COMPARISON OF CARDIOVASCULAR RISK FACTORS PREVALENCE AMONG CATHOLICS AND SEVENTH-DAY ADVENTISTS LIVING IN SOUTHERN POLANDIntroduction. A review literature concerning the religious affiliation and that of cardiovascular disease did not show any clear correlations between these variables.Aim. To determine selected cardiovascular risk factors and the risk of a cardiovascular event among Seventh-day Adventists (SDA) and Catholics.Material and Methods. A cross-sectional study was carried out in the years 2014-2015 among 252 people, including 118 Seventh-day Adventists and 134 Catholics over 18 years of age, residents of southern Poland. The results of the following were analysed: anthropometric measurements, an interview questionnaire, physical examination and laboratory tests, as well as the SCORE scale.Results. The mean concentration of homocysteine and triglycerides in Catholics was significantly higher than in Adventists. Adventists had significantly higher blood pressure and mean HDL cholesterol concentration than Catholics. On the basis of BMI, overweight and obesity were ascertained in a somewhat greater percentage of Catholics than Adventists, and on the basis of waist circumference, android obesity was found to be more common in Catholics than in Adventists.Conclusions. Based on the SCORE scale, the risk of a cardiovascular event was significantly higher in Catholics than in Adventists.